Pemanfaatan Media PowerPoint dalam Pembelajaran Fiqih - Mustakim, Ali; Romdloni, Romdloni; Ahid, Muhammad (Prodi Pendidikan Agama Islam, 2023)
This research aims to determine the use of Power Point media in learning fiqh at MAN 1 OKU Timur. This aim is motivated by developments in learning media technology. The research method used is descriptive research with a qualitative approach that seeks to describe symptoms, events and incidents that are currently occurring. In the data collection process, researchers used several techniques, namely observation, interviews and documentation techniques. The data processing techniques used are editing, description and verification. Meanwhile, data analysis uses qualitative descriptive analysis. The results of this research show: 1) Implementation of the use of PowerPoint media in fiqh learning at MAN 1 OKU Timur through the stages of learning planning, learning implementation and learning evaluation. 2) Supporting factors for the fiqh learning process using PowerPoint media are the availability of tools used for Power Point such as LCDs and projectors, the availability of teaching materials and other adequate facilities.